(untitled) (World Economics and Finance Bulletin, 2023)
The current research was interested in studying the nature of the relationship between the variables (marketing intelligence and customer satisfaction) in terms of correlation and influence. The research was applied in terms of the field aspect at the Rotana Rayhana Karbala Hotel in the holy city of Karbala and targeting the sample members represented by the group of workers in this hotel and seeking to obtain answers to the tool The research is a questionnaire in order to find out their opinions about its content. The answers were analyzed using the SPSS statistical program to determine the nature of the relationship and influence between the variables. The statistical analysis led to acceptance of the research hypotheses, which support the nature of the relationships between the research variables. In addition, the research was concerned with providing a set of recommendations that emphasize the importance of the research variables and serve the field aspect of the hotel.